2021
DOI: 10.4103/jcd.jcd_433_21
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory efficacy of petasin-incorporated zinc oxide eugenol sealer – An in vivo zebrafish study

Abstract: Background: The eugenol from zinc oxide eugenol (ZnOE) sealer tends to diffuse to the periapical region resulting in inflammation. Several modifications of ZnOE sealer have been formulated to minimize the inflammatory potential of the ZnOE sealer. Petasites hybridus contains petasin which possesses anti-inflammatory property used in treatment of migraine and allergic rhinitis. Aim: The aim of the study was to evaluate the anti-inflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As stated by Vinola et al, and various authors 15% petasin demonstrated potent anti-inflammatory, analgesic, and anti-spasmodic properties attributed to its sequiterpene content [ 17 , 33 , 34 ]. Regarding pachymic acid, Arun et al found that 0.5% exhibited profound anti-inflammatory effects by acting on reactive oxygen species (ROS) formation, thereby reducing sealer-induced cytotoxicity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Vinola et al, and various authors 15% petasin demonstrated potent anti-inflammatory, analgesic, and anti-spasmodic properties attributed to its sequiterpene content [ 17 , 33 , 34 ]. Regarding pachymic acid, Arun et al found that 0.5% exhibited profound anti-inflammatory effects by acting on reactive oxygen species (ROS) formation, thereby reducing sealer-induced cytotoxicity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petasin and isopetasin, two of the main bioactive compounds in PJE, have been shown to inhibit adipocyte differentiation and adipogenesis in vitro by suppressing the expression of adipogenic transcription factors [ 15 , 36 , 37 ]. In addition, these compounds have been reported to exhibit anti-inflammatory activity by inhibiting the leukotriene synthesis in human macrophages, neutrophils, and eosinophils, and thereby suppressing the inflammatory process [ 38 ]. These findings suggest that the anti-obesity effects of PJE are mediated, at least in part, through its active compounds, petasin, isopetasin, as well as several polyphenolics.…”
Section: Discussionmentioning
confidence: 99%